Macroscopic criteria for the deformation and fracture of iron based alloys - Dina V. Orlova; Alexey G. Lunev; Lidiya V. Danilova; Lev B. Zuev (Fracture and Structural Integrity)
In the article the deformation of different steels is analyzed using the autowave theory of plasticity. The article considers the possible use of an autowave model to formulate criteria for the structural strength of materials and elastic-plastic transition. The time and place of future fracture for steel samples are shown can be predicted before visible necking takes place by using the kinetic dependencies of localized plasticity domains at the prefracture stage. The results show that during elastic-plastic transition in lowcarbon steel, there is the break of the curve for the ultrasound velocity versus deformation, which can serve as an acoustic criterion of irreversible deformation for the pressure treatment of metals, the operation and nondestructive testing of products and structures